Australian languages : classification and the comparative method - Bowern, Claire, 1977-; Koch, Harold James (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2004)
This book addresses controversial issues in the application of the comparative method to the languages of Australia which have recently come to international prominence. Are these languages 'different' in ways that challenge the fundamental assumptions of historical linguistics? Can subgrouping be successfully undertaken using the Comparative Method? Is the genetic construct of a far-flung 'Pama-Nyungan' language family supportable by classic methods of reconstruction? Contrary to increasingly established views of the Australian scene, this book makes a major contribution to the demonstration.